Culture and Intraracial Wage Inequality Among America's African Diaspora - Mason, Patrick L (American Economic Review, 2010)
At the height of the US civil rights movement in the mid-1960s foreign-born persons were less than one percent of the African American popu lation. Today, 12 percent of America's African Diaspora work force consists of immigrants, and three percent are Hispanic. Some black immi grants?for example, Haitians and Spanish speaking Caribbean immigrants?have lower earnings and lower productivity-linked charac teristics than native African Americans. Other